Enhancing emergency evacuation response of late evacuees: Revisiting the case of Australian Black Saturday bushfire - Shahparvari, Shahrooz; Chhetri, Prem; Abbasi, Babak; Abareshi, Ahmad (Transportation research. Part E, Logistics and transportation review, 2016)
•The proposed model is policy relevance – “Stay or Go recommendations” policy applied in Australia.•The model generates evacuation plans incorporating uncertainty disruptions in road and shelter accessibilities.•The model considers capacitated multi-location, multi-routing, multi-vehicles types.•The proposed approach is applied to a large-scale real case study within in Victoria, Australia. This paper develops a multi-objective integer programming model to support tactical planning decision-making during a short-notice evacuation using the situated context of the 2009 Black Saturday bushfires in Victoria. Various bushfire scenarios and sensitivity analysis considering short time windows, availability of resources and road disruptions were implemented to demonstrate the robustness and reliability of the model. The ε-constraint technique was applied to solve the problem. Results showed that it would be possible to evacuate all late evacuees during the Black Saturday bushfire events, even if one or two resources are disrupted within the hard time window constraint.